Stability evaluation of tunnels in steeply dipping layered rock mass using numerical models: a case study - Eleyas Assefa; Kidusyared Tilahun; Siraj Mulugeta Assefa; Nagessa Zerihun Jilo; Lysandros Pantelidis; Costas Sachpazis (Scientific Reports)
Abstract Tunnel stability is a critical factor in complex geological conditions, particularly in rock masses with steeply dipping layers. Among widely used methods, the Convergence–Confinement Method (CCM), a prevalent two-dimensional (2D) approach, effectively captures the relaxation process preceding support installation. However, most studies focus on homogeneous or horizontally layered rock masses, often overlooking the influence of steeply dipping, and layered geological formations. This study investigates the influence of layer dip angle and layer position on the stress relaxation factor (λ) and tunnel deformation through parametric analysis. The results indicate that λ increases with steeper dip angles, such as 60° and 90°, and decreases as the layers are positioned farther from the tunnel center, for instance, two tunnel widths above or below. Tunnel deformation is highly influenced by these factors, and the optimized λ values allow the 2D Convergence–Confinement Method (CCM) predictions to closely correlate with 3D simulation results. These findings enhance the applicability of the Convergence–Confinement Method (CCM) for tunnel stability analysis in steeply dipping, layered rock masses.